2018
DOI: 10.1186/s13059-018-1547-5
|View full text |Cite
|
Sign up to set email alerts
|

SCoPE-MS: mass spectrometry of single mammalian cells quantifies proteome heterogeneity during cell differentiation

Abstract: Some exciting biological questions require quantifying thousands of proteins in single cells. To achieve this goal, we develop Single Cell ProtEomics by Mass Spectrometry (SCoPE-MS) and validate its ability to identify distinct human cancer cell types based on their proteomes. We use SCoPE-MS to quantify over a thousand proteins in differentiating mouse embryonic stem cells. The single-cell proteomes enable us to deconstruct cell populations and infer protein abundance relationships. Comparison between single-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
772
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 701 publications
(782 citation statements)
references
References 57 publications
8
772
0
2
Order By: Relevance
“…Dorus et al, 2006;Baker et al, 2008;Poland et al, 2011;Skerget et al, 2013;Amaral et al, 2014;Ma et al, 2014;Whittington et al, 2015;Degner et al, 2019). As methods for single-cell analysis improve (Budnik et al, 2018), single-cell proteomics could be used to inventory sperm composition across the entire life history of sperm in the FRT. The consequent determination of gains, losses and modifications of sperm (or sperm-associated seminal or female) proteins will provide molecular precision to our understanding of the sequence of changes in sperm as they reside in the FRT.…”
Section: Future Directionsmentioning
confidence: 99%
“…Dorus et al, 2006;Baker et al, 2008;Poland et al, 2011;Skerget et al, 2013;Amaral et al, 2014;Ma et al, 2014;Whittington et al, 2015;Degner et al, 2019). As methods for single-cell analysis improve (Budnik et al, 2018), single-cell proteomics could be used to inventory sperm composition across the entire life history of sperm in the FRT. The consequent determination of gains, losses and modifications of sperm (or sperm-associated seminal or female) proteins will provide molecular precision to our understanding of the sequence of changes in sperm as they reside in the FRT.…”
Section: Future Directionsmentioning
confidence: 99%
“…Next to the development of dedicated low-input sample preparation methods [1][2][3][4], which aim at reducing sample losses prior to analysis, changes to the chromatographic support material have recently been identified key to the sensitive profiling of low-input proteomics samples by nano-HPLC-ESI-MS/MS [5,6].…”
Section: Technical Briefmentioning
confidence: 99%
“…38 A comprehensive review of LC-MS/MS QC and optimization tools has been published by Bittremieux et al 39 We found these tools useful in developing Single-Cell Proteomics by Mass Spectrometry (SCoPE-MS), which combines TMT-labeled peptides from single cells with a TMT-labeled carrier channel to enable quantifying proteins across many single cells. [25][26][27]40 However, none of these tools provided all of the metrics needed for optimizating our SCoPE-MS analysis. 40 This motivated us to develop DO-MS, a highly modular and interactive environment for optimizing ultra-sensitive LC-MS/MS methods.…”
Section: Introductionmentioning
confidence: 99%